Adolescent idiopathic scoliosis: current concepts on neurological and muscular etiologies. Issue 1 (December 2016) - Wajchenberg, Marcelo; Astur, Nelson; Kanas, Michel; Martins, Délio
Abstract Adolescent idiopathic scoliosis (AIS) is a frequent disease but its etiology remains unknown. Gender prevalence in females is already known and there are many suggested hypotheses to explain its origin and manifestation, like associated neurologic, muscular and connective tissue disorders. Literature reports have tried to analyze disease prevalence in selected populations, possible ways of inheritance, related genes location and their polymorphisms, which may play a role in the development of the deformity. The purpose of this paper is to review and update concepts on the origin and genetic influence on AIS.